Organized crime, foreign investment and economic growth : the Latin American case (2012)
Latin America has been seen over the years as a violent region. Organized crime has been a major factor contributing to that perception. Crime not only makes daily life more dangerous for citizens of a country, but can even challenge the viability of governments. Crime fighting efforts drain state resources, threaten the delivery of public services, and might have a negative influence on institutional stability and business environment. The purpose of this paper is to extend the empirical framework of Bengoa and Sánchez-Robles (2002) to cover the relationship between organized crime, foreign direct investment (FDI) and growth. Although the relationship between organized crime and FDI is not widely discussed in the literature, it can be argued that there is a very important channel through which this relationship may exist: institutional instability of states and viability of governments